Learning Curve of Ex Vivo Liver Resection and Autotransplantation in Treating End-Stage Hepatic Alveolar Echinococcosis: A RA-CUSUM Analysis - Qiu, Yiwen; Yang, Xianwei; Wang, Tao; Shen, Shu; Yang, Yi; Huang, Bin; Wang, Wentao (Frontiers in Surgery, 2021)
Background: This retrospective study aimed to evaluate the safety and learning curve of ex vivo liver resection and autotransplantation (ELRA). Methods: A total of 102 consecutive end-stage HAE patients who underwent ELRA between 2014 and 2020 in West China Hospital were enrolled. The primary endpoint was major postoperative complications (comprehensive complication index, CCI > 26). The ELRA learning curve was evaluated using risk-adjusted cumulative sum (RA-CUSUM) methods. The learning phases were determined based on RA-CUSUM analysis and tested for their association with intra- and post-operative endpoints. Results: The median surgery time was 738 (659–818) min, with a median blood loss of 2,250 (1,600–3,000) ml. The overall incidence of major morbidity was 38.24% (39/102). Risk-adjusted cumulative sum analysis demonstrated a learning curve of 53 ELRAs for major postoperative complications. The learning phase showed a significant association with the hemodynamic unstable time (HR −30.29, 95% CI −43.32, −17.25, P < 0.0001), reimplantation time (HR −13.92, 95% CI −23.17, −4.67, P = 0.004), total postoperative stay (HR −6.87, 95% CI −11.33, −2.41, P = 0.0033), and postoperative major morbidity (HR 0.25, 95% CI 0.09, 0.68, p = 0.007) when adjusted for age, disease course, liver function, and remote metastasis. Discussion:Ex vivo liver resection and autotransplantation is feasible and safe with a learning curve of 53 cases for major postoperative complications.